2021
DOI: 10.31004/basicedu.v5i6.1556
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Cakupan Literasi Sains dalam Buku Siswa Kelas V Tema 4 Karya Ari Subekti di Sekolah Dasar

Abstract: Literasi sains merupakan suatu kemampuan yang harus dimiliki oleh peserta didik untuk memahami lingkungan hidup dan permasalahan yang dihadapi oleh masyarakat. Dengan demikan, untuk mengetahui ada tidaknya literasi sains maka perlu dilakukan analisis cakupan literasi sains pada buku siswa. Tujuan penelitian untuk menganalisis cakupan literasi sains pada buku siswa kelas V tema 4 karya Ari Subekti. Penelitian menggunakan pendekatan kualitatif dengan desain analisis isi Teknik pengumpulan data melalui studi doku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
(8 reference statements)
1
5
0
1
Order By: Relevance
“…That is, aspects of science as the body of science appear more often in books than other aspects of scientific literacy. In line with study of Utami and Desstya [4] that in this aspect it has the highest average percentage level of the other three aspects of scientific literacy with a value of 79.16% and the total score of the sub-themes is 38. This also showed that the material in the fifth-grade student book by Ari Subekti for elementary school emphasizes material that is a science product.…”
Section: Science Is the Body Of Sciencesupporting
confidence: 75%
See 3 more Smart Citations
“…That is, aspects of science as the body of science appear more often in books than other aspects of scientific literacy. In line with study of Utami and Desstya [4] that in this aspect it has the highest average percentage level of the other three aspects of scientific literacy with a value of 79.16% and the total score of the sub-themes is 38. This also showed that the material in the fifth-grade student book by Ari Subekti for elementary school emphasizes material that is a science product.…”
Section: Science Is the Body Of Sciencesupporting
confidence: 75%
“…Showed the results that the importance of the scientific aspect as the interaction of science, technology and society is not balanced from the analysis that has been carried out by the author getting a total score of 39 and an average percentage of 27.08% [4]. From this it could be said that the aspect of science as the Interaction of Science, Technology and Society is the smallest percentage compared to other elements.…”
Section: Interaction Of Science Technology and Societymentioning
confidence: 96%
See 2 more Smart Citations
“…(Lestari et al, 2021) did research on the effect of the culture of literacy on science learning results at the elementary school level. (Utami & Desstya, 2021) also conducted a study on analysis of science literacy domain in the textbooks of 5th-grade elementary school, particularly on theme 4 written by Ari Subekti at elementary school. Moreover, (Tahmidaten & Krismanto, 2020) did a study on literacy with focus problems and solutions of reading culture in Indonesia.…”
Section: Introductionmentioning
confidence: 99%